Application of shared parenting in Malaysia: appraising the Australian experience - Ali, Suzana; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah (University Putra Malaysia, 2017)
Internationally, shared parenting has been highlighted and agreed to be the best method in protecting the welfare of the child. The religion of Islam also promotes the concept of shared parenting to ensure that the welfare of the child is well protected. In Malaysia, legislation on child custody emphasises that the welfare of the child shall be given paramount consideration but there are no provisions on shared parenting and specific guidelines on its application. An amendment was made to the laws to include a provision on equal parental rights but it does not directly relate to the principle of shared parenting. The vagueness of the law and the lack of proper guidelines in relation to shared parenting open the doors for the courts to render inconsistent decisions in determining custodial rights, and this often results in decisions in favour of sole custody. The absence of specific laws on shared parenting has also caused difficulties for parents in cooperating for the sake of their children. They tend to stress on their conflicts and fight for their rights rather than focus on the welfare of the children. This paper seeks to discuss the current position of shared parenting after marital separation in Malaysia. As Malaysia practises a dual legal system, this paper will also examine the suitability of applying the shared parenting principle in both systems. A brief comparative review will also be made of Australian law and policies, which are more advanced on the subject of shared parenting.